A Computational Study on Mixed Convection Heat Transfer in an Inclined Rectangular Channel under Imposed Local Flow Modulation (Journal of Chemical Engineering, 2017)
Numerical investigation of mixed convection heat transfer in an inclined 2D rectangular channel provided with partially heated bottom wall and a constant low temperature upper wall has been performed. The heated section of the bottom wall i.e. the heaters are maintained with constant heat flux and separated from each other by adiabatic segments. A fully developed parabolic velocity profile at constant low temperature is induced at the inlet. To enhance the heat transfer from the heaters, local flow field in the channel is modulated by placing circular cylinders rotating in counterclockwise direction (aiding flow) above each heater along the channel centerline. The fluid and the thermal fields within the rectangular channel are governed by the two-dimensional Navier-Stokes and Energy equations that have been solved by adapting Galerkin finite element method. The governing parameters of the present problem such as Reynolds number (Re) and Grashof number (Gr) are varied in the range of 1 ≤ Re ≤ 100 and 103 ≤ Gr ≤ 105. Air has been considered as working fluid having a Prandtl number, Pr = 0.71. In addition to these governing parameters, the inclination angle of the channel (α) and the speed ratio (ξ) that is the ratio of peripheral speed of the rotating cylinder and the maximum inlet flow velocity is also varied in the range of 0° ≤ α ≤ 90° and 0.5 ≤ ξ ≤ 2.0 respectively. The thermal and the fluid fields are visualized via the isotherm and the streamline plots. The efficacy of local flow modulation with rotating cylinder for heat transfer enhancement has been estimated in terms of normalized average Nusselt number over the heaters as Nu/Nunc, where Nu and Nunc represents the average Nusselt number with and without flow modulation respectively. Results obtain in the present study reveals that, for very weak flow (Re = 1), flow modulation results in lower heat transfer particularly at lower values of Gr on the contrary for moderate and higher values of Re (10, 100), flow modulation has been found to result in higher heat transfer particularly at lower values of Gr. For example, at Re = 100 and α= 0°, about 32% to 55% enhancement in heat transfer has been obtained for 103≤ Gr ≤ 105. Variation in heat transfer enhancement through flow modulation has also been noticed for different channel inclination angle (α) for various system configurations.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 43-50